2008
DOI: 10.1128/aem.02568-07
|View full text |Cite
|
Sign up to set email alerts
|

Relative Abundance ofBacteroidesspp. in Stools and Wastewaters as Determined by Hierarchical Oligonucleotide Primer Extension

Abstract: A molecular method, termed hierarchical oligonucleotide primer extension (HOPE), was used to determine the relative abundances of predominant Bacteroides spp. present in fecal microbiota and wastewaters. For this analysis, genomic DNA in feces of healthy human adults, bovines, and swine and in wastewaters was extracted and total bacterial 16S rRNA genes were PCR amplified and used as the DNA templates for HOPE. Nineteen oligonucleotide primers were designed to detect 14 Bacteroides spp. at different hierarchic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
44
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 49 publications
(48 citation statements)
references
References 45 publications
3
44
1
Order By: Relevance
“…The lower detection sensitivity of the Bifidobacterium-targeting primers than those obtained in previous studies (5,19) may be due to the high GC content of DNA templates. As Bifidobacterium spp.…”
contrasting
confidence: 49%
See 2 more Smart Citations
“…The lower detection sensitivity of the Bifidobacterium-targeting primers than those obtained in previous studies (5,19) may be due to the high GC content of DNA templates. As Bifidobacterium spp.…”
contrasting
confidence: 49%
“…A subsequent study demonstrated that HOPE can be used for rapid and specific determination of Bacteroides spp. present in feces and wastewaters at different taxonomical levels (5). It also has the versatility to be expanded to include other bacterial groups.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…High levels of toxin lyses cells as the pores formed by the toxin allow cytoplasmic contents to leak out (24). Of interest was the identification of a hypothetical protein belonging to Bacteroides eggerthii, a member of the Bacteroides genus that has been isolated from human feces (3,13). The relevance of identifying this protein from C. ureolyticus was that the bacterium was previously a member of the Bacteroides genus.…”
Section: Effect Of C Ureolyticus Unswcd Infection and Cytokines On Imentioning
confidence: 99%
“…This primer was included in all reaction mixtures and was used as an internal standard for comparison of Bacteroides populations in a wastewater treatment plant, in stools (10), and in wastewater samples (41).…”
Section: Vol 75 2009 Snupe For Detection and Typing Of Phylogeneticmentioning
confidence: 99%